Low-Cost, High-Fidelity Ultrasound Phantom Gels for Regional Anesthesia Training Programs - Loreto Lollo; Agnes R. Stogicza (Association of American Medical Colleges, 2012)
Abstract This module details the construction of low-cost, high-fidelity phantom gels that can be inexpensively produced and reused. These gels mimic the anatomic structures pertinent to performance of upper and lower extremity peripheral nerve blockade under ultrasound guidance. A review of the anatomy and specific procedure to be practiced is presented in small groups prior to using the models. This presentation can be done as a single review of all the techniques at one time or a separate procedural review can be done at the skill station for the specific nerve block being instructed. Implementation of the phantom gels requires an hour to assemble the anatomic backbone and then 5 minutes to prepare the gel for placement in the molds. The models are then refrigerated overnight and can be removed from their molds if necessary, The anatomic and procedural review is 2-3 minutes in duration for each skill station and the use of multiple simultaneous images of the surface anatomy, deep anatomy, and ultrasound image allows the trainee to integrate the ultrasound images observed during the simulation with the anatomic structures reviewed. Three sessions have been completed with anesthesiology faculty, certified nurse anesthetists, and senior level anesthesia residents. The gels have been integrated into a core regional anesthesia teaching module that will allow all members of the department access to the simulations at 6 month intervals.